2021
DOI: 10.3390/ijms22062833
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cold Atmospheric Pressure Plasma on Germination Parameters, Enzyme Activities and Induction of DNA Damage in Barley

Abstract: Climate change, environmental pollution and pathogen resistance to available chemical agents are part of the problems that the food industry has to face in order to ensure healthy food for people and livestock. One of the promising solutions to these problems is the use of cold atmospheric pressure plasma (CAPP). Plasma is suitable for efficient surface decontamination of seeds and food products, germination enhancement and obtaining higher yields in agricultural production. However, the plasma effects vary du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 73 publications
4
18
0
Order By: Relevance
“…Moreover, the available data are focused mainly on the direct plasma treatment. For example, Peťková et al [ 51 ] showed a positive effect of NTP generated in three different atmospheres with short exposure time (10–30 s) on barley grains, while longer exposure time (60 s and 180 s) caused an opposite effect on protease activity. These results were also confirmed by Švubová et al [ 20 , 49 ] on pea seeds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the available data are focused mainly on the direct plasma treatment. For example, Peťková et al [ 51 ] showed a positive effect of NTP generated in three different atmospheres with short exposure time (10–30 s) on barley grains, while longer exposure time (60 s and 180 s) caused an opposite effect on protease activity. These results were also confirmed by Švubová et al [ 20 , 49 ] on pea seeds.…”
Section: Resultsmentioning
confidence: 99%
“…However, in this study, younger plants (3-day-old seedlings) were used for experiments, and this could be the reason why the DNA damage was higher (also in control samples). DNA damage in 7-day-old barley seedlings after direct plasma treatment was analysed in the study of Peťková et al [ 51 ]. A statistically significant increase in DNA damage was observed in all samples treated with plasma generated in nitrogen, oxygen or ambient air for 10–60 s. These damages were caused mainly by single-strand breaks and purine oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al [25] reported that argon plasma positively affected soybean seed germination as well as the growth and development of young seedlings by regulating the level of demethylation of genes associated with energy metabolism. Acceleration of the germination process by positively influencing the activity of lytic enzymes (proteases, glucanases, amylases) is also presented in the works by Sadhu et al [62] for mung beans, Švubová et al [19] for pea seeds, Švubová et al [20] for soybean, and Pet'ková et al [21] for barley grains. The effective mobilization of storage substances and the increase of the soluble sugar and protein content in oilseed rape seedlings are documented by Ling et al [63].…”
Section: Capp Application (S)mentioning
confidence: 93%
“…Sci. 2021, 22, 8509 9 of 21 of lytic enzymes (proteases, glucanases, amylases) is also presented in the works by Sadhu et al [62] for mung beans, Švubová et al [19] for pea seeds, Švubová et al [20] for soybean, and Peťková et al [21] for barley grains. The effective mobilization of storage substances and the increase of the soluble sugar and protein content in oilseed rape seedlings are documented by Ling et al [63].…”
Section: Capp Application (S)mentioning
confidence: 95%
See 1 more Smart Citation